Gene polymorphism of TLR4 (rs10759931) in patients with SARS-CoV-2 and its association with cognitive impairment - Abdula-Samad, Asmaa A.; Fadhil, Hula Y. (Iraqi Journal of Science, 2025)
This research examined the presence of the rs10759931 single nucleotide polymorphism (SNP) in the TLR4 gene among COVID-19 patients. Additionally, it evaluated how this genetic variation influenced cognitive difficulties in individuals recovering from the disease. This Case–control study (60 patients, 30 recovered, and 50 controls) investigates the G/A genotype of rs10759931 in all studied groups, using a conventional polymerase chain reaction with an allele-specific primer method. Results showed a median of ages was significant raising in age accompanied by severe cases (p =0.003) and more than 50% of the moderate infections in the youth category. Regarding the recovered individual’s occurrence six cases along with ages median of 49.5 (45.8-57) males and females with a history of mild to moderate infection. When comparing the clinical severity, allele and genotype frequencies of the G/A rs10759931 TLR4 polymorphism showed no statistically significant differences between COVID-19 patients and controls (OR = 1.22; 95% CI = 0.60–2.49; p = 0.715). In recovered individuals with cognitive impairment, despite the occurrence of 66.7% of cognitive impairment in the GG genotype, there is no significant difference compared to intact recovered individuals (OR = 0.21; 95% CI = 0.03–1.39; p = 0.163). In conclusion, G/A rs10759931 of TLR4 required more information to explore their role in cognitive impairment and infection severity.